Soil management and climate change effects on organic carbon, nitrogen dynamics, and greenhouse gas emissions - Muñoz, María Ángeles; Zornoza, Raúl (Academic Press, 2018)
Soil Management and Climate Change: Effects on Organic Carbon, Nitrogen Dynamics, and Greenhouse Gas Emissions provides a state of the art overview of recent findings and future research challenges regarding physical, chemical and biological processes controlling soil carbon, nitrogen dynamic and greenhouse gas emissions from soils. This book is for students and academics in soil science and environmental science, land managers, public administrators and legislators, and will increase understanding of organic matter preservation in soil and mitigation of greenhouse gas emissions. Given the central role soil plays on the global carbon (C) and nitrogen (N) cycles and its impact on greenhouse gas emissions, there is an urgent need to increase our common understanding about sources, mechanisms and processes that regulate organic matter mineralization and stabilization, and to identify those management practices and processes which mitigate greenhouse gas emissions, helping increase organic matter stabilization with suitable supplies of available N.--Provided by publisher.